Impact of Different Regimens of Fluoridated Dentifrice Application on the pH and Inorganic Composition in an Oral Microcosm Biofilm Model - Patrícia de Lourdes Budoia de Carvalho; Juliano Pelim Pessan; Bruna do Amaral; Amanda Costa Troncha; Samuel Campos Sousa; Douglas Roberto Monteiro; Thayse Yumi Hosida; Alberto Carlos Botazzo Delbem; Caio Sampaio (Microorganisms)
This study evaluated the pH, fluoride (F), and calcium (Ca) concentrations in saliva-derived microcosm biofilms following treatments with dentifrices applied at different amounts and F concentration. Human saliva was inoculated into McBain culture medium, and treatments were applied at 72/78/96 h (1 min). Fluoridated dentifrices containing 550 or 1100 ppm F (550F and 1100F, respectively) were used at the following combinations (intensities): (i-1) 550F/0.08 g or 1100F/0.04 g; (i-2) 550F/0.16 g or 1100F/0.08 g; (i-3) 550F/0.32 g or 1100F/0.16 g. A negative control (fluoride-free dentifrice—PLA) was also included. Biofilm F and Ca were measured with an ion-selective electrode and colorimetrically, respectively, while pH in the culture medium was measured with a pH electrode. Data were subjected to ANOVA and Student–Newman–Keuls’ test (p < 0.05). F-dentifrices did not significantly alter pH compared to PLA, except for 1100F at i-3. Biofilm F levels at i-1 and i-2 were comparable, for both 550F and 1100F, while 1100F at i-3 led to the highest biofilm F concentration. All F-groups showed significantly higher Ca levels than PLA, especially at i-2 and i-3. In conclusion, the interplay between dentifrice amount and F concentration was more influential on the biofilm’s inorganic composition and pH than either variable alone.